2015
DOI: 10.1177/0961203314559634
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacteria and autoimmunity

Abstract: Mycobacterial infections can cause a variety of different manifestations. The increasing incidence of these infections worldwide brought another medical dilemma: immunological manifestations characterized by the presence of many autoantibodies and concomitant presence of autoimmune diseases. The burden of tuberculosis reactivation that emerged with immunosuppressive therapy worsened with the growing use of biological disease-modifying antirheumatic drugs (DMARDs). This review will address the relationship betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 88 publications
(131 reference statements)
1
18
0
Order By: Relevance
“…Further, the present case exemplifies the already described association between mycobacterial infections and autoimmune phenomena, including the emergence of diverse autoantibodies, such as ANA, antineutrophil cytoplasmic antibodies, and anti-SSA/Ro antibodies ( 15 ). Recently, Chao et al have described a significant association between non-tuberculous mycobacterial infection and SS ( 16 ), which can be reflecting the pathogenic involvement of mycobacterial infections in SS.…”
Section: Discussionsupporting
confidence: 80%
“…Further, the present case exemplifies the already described association between mycobacterial infections and autoimmune phenomena, including the emergence of diverse autoantibodies, such as ANA, antineutrophil cytoplasmic antibodies, and anti-SSA/Ro antibodies ( 15 ). Recently, Chao et al have described a significant association between non-tuberculous mycobacterial infection and SS ( 16 ), which can be reflecting the pathogenic involvement of mycobacterial infections in SS.…”
Section: Discussionsupporting
confidence: 80%
“…The patient in this report had a medical history of pelvic tuberculosis and oligomenorrhea or amenorrhea occurred after anti-tuberculosis therapy. While mycobacterial tuberculosis infections are known to induce the development of autoantibodies and even autoimmune diseases [20, 21]. In a recent study of ROS case, it demonstrated that IgG/IgM-antibodies directed against some forms of gonadotropins were found in serum and respective antibodies in this serum only react with some but not all forms of FSH [13].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, we cannot exclude the possibility of a T-cell independent humoral immune response against retina antigens nor potential molecular mimicry as has been demonstrated to exist for mycobacterial heat-shock protein-65 and medium molecular weight neurofilament (NF-M). 25,26 Discrepancies between autoantibody positivity and the absence of detectable circulating autoreactive T-cells have been observed in other disease entities as well, for instance in anti-Hu antibody-associated paraneoplastic neurological syndromes. 27 The high ARA prevalence observed in our current study might be an overestimation as the number of patients per uveitis group was small.…”
Section: Discussionmentioning
confidence: 99%